Innovative chemical synthesis and conformational hints on the lipopeptide liraglutide. (30th May 2016) - Guryanov, Ivan; Bondesan, Alex; Visentini, Dario; Orlandin, Andrea; Biondi, Barbara; Toniolo, Claudio; Formaggio, Fernando; Ricci, Antonio; Zanon, Jacopo; Cabri, Walter
Abstract : Liraglutide is a new generation lipopeptide drug used for the treatment of type II diabetes. In this work, we describe new approaches for its preparation fully by chemical methods. The key step of these strategies is the synthesis in solution of the Lys/γ‐Glu building block, Fmoc‐Lys‐(Pal‐γ‐Glu‐O t Bu)‐OH, in which Lys and Glu residues are linked through their side chains and γ‐Glu is N α ‐palmitoylated. This dipeptide derivative is then inserted into the peptide sequence on solid phase. As liraglutide is obtained with great purity and high yield, our approach can be particularly attractive for an industrial production. We also report here the results of a circular dichroism conformational analysis in a membrane mimetic environment that offers new insights into the mechanism of action of liraglutide. Copyright © 2016 European Peptide Society and John Wiley & Sons, Ltd. Abstract : Liraglutide is a new generation lipopeptide drug used for the treatment of type II diabetes. Here, we describe new approaches for its preparation. The key step of these strategies is the synthesis in solution of the palmitoylated Lys/ γ ‐Glu building block, Fmoc‐Lys(Pal‐ γ ‐Glu‐O t Bu)‐OH, and its following insertion into the peptide sequence on solid phase. We also report here the results of a circular dichroism conformational analysis in a membrane mimetic environment that offers new insights into the mechanism of action of liraglutide.